Educational Research in the Undergraduate Foreign Language Teaching Program at Universidad de Pamplona - Martínez Cáceres, Magdaleydy (Íkala, Revista de Lenguaje y Cultura, 2016)
The importance of the educational research does not only contribute to close the existing knowledge gap in the field, but also helps to enhance the teachers’ critical view on their teaching process; to have a better understanding of the educational phenomena, to improve the decision making process and to formulate educational policies to improve teaching and learning. The main purpose of this case study was to provide an overview on the research projects that have been conducted in the major of French in Bachelor of Arts in Foreign Languages at the Universidad de Pamplona. Data was collected through the undergraduate researchers’ journals, surveys, and video recordings on their experiences when writing a proposal, collecting and analyzing data for their projects. Based on a typological analysis, this case study reports findings on how educational research has contributed on the foreign language pre-service teachers training process; their interests and difficulties.